Small-molecule mediated MuRF1 inhibition protects from doxorubicin-induced cardiac atrophy and contractile dysfunction - Alves, Paula; Cruz, André; Adams, Volker; Moriscot, Anselmo S.; Labeit, Siegfried (European journal of pharmacology, 2024)
Cancer chemotherapy induces cell stress in rapidly dividing cancer cells to trigger their growth arrest and apoptosis. However, adverse effects related to cardiotoxicity underpinned by a limited regenerative potential of the heart limits clinical application: In particular, chemotherapy with doxorubicin (DOXO) causes acute heart injury that can transition to persisting cardiomyopathy (DOXO-CM). Here, we tested if MuRF1 inhibition (“MuRFi”) was able to attenuate DOXO-CM. To mimic DOXO chemotherapy, we treated mice over four weeks with five DOXO injections, resulting in a cumulative dosage of 25 mg/kg. At day 28, mice had lower body and heart weights, reduced cardiac cross-sectional myofibrillar areas (CSAs), and disturbed functional ejection fractions (EFs) and fractional shortenings (FS) as indicated by echocardiography (ECHO). In contrast, mice with a 1 g/kg Myomed#205 spiked diet, a previously described experimental MuRFi therapy, showed lower DOXO-CM at day 28, and also reduced acute DOXO cardiac injury at day 7 (single DOXO dose; 15 mg/kg). Underlying molecular signatures using Western blot (WB) assays showed at day 28 reduced phospho-AKT (AKTp) and phospo-4EBP1 (4 EBP1p) levels following DOXO that were normalized following MuRFi treatment. Taken together, our data suggest that MuRFi treatment is suitable to attenuate DOXO-CM by preserving AKTp and 4 EBP1p levels in DOXO stressed cardiomyocytes, thereby supporting de novo protein translation and cardiomyocyte survival under translational arrest stress.